A Short Note on Visiting Cards from Wood Veneers - Gupta, R. C.; Lala, M. K. (Indian Forester, 1979)
Visiting cards were made at the Composite Wood Branch of the Forest Research Institute from wood veneers of three different species using three different glues. Veneers were either rotary peeled or sliced in thickness of 0.25 mm. It was noticed that for getting good grains on cards sliced veneers were better than rotary peeled veneers. Three ply construction was tried, but it was found that these cards were stiff and thick and hence this method was abandoned. Another method using two veneers with a core of glue coated kraft paper was adopted and it was found that these cards using Animal glue have shown no delamination even after six months and do not pose any printing problems. From these experiments it appears that the veneer paper laminates hold a good promise for use in visiting cards.